Analisis dan Implementasi Sistem Antrian Digital Berbasis Web untuk Optimalisasi Layanan Perbankan Modern - Alifya Aisya, Alifya Aisya; Bastio, Aldrik; Pandiangan, Daniel; Niska, Debi Yandra (TIN: Terapan Informatika Nusantara, 2025)
This study aims to analyze and develop a web-based digital queuing system designed to significantly enhance the efficiency of banking services in the digital age. The urgent problem identified is the suboptimal management of customer queues, which frequently leads to prolonged waiting times and ultimately diminishes customer satisfaction with the bank's services. We constructed this system using the foundational web technologies of HTML, CSS, and JavaScript, primarily targeting the creation of an interface that is user-friendly, visually comfortable, and accessible from any gadget. The research was conducted at Bank Nusantara Branch in Medan. The methodology involved direct observation of the current manual queuing process, coupled with brief discussions (interviews) with several customers and staff to accurately grasp the specific needs. The key contribution of this study is the successful creation of a comprehensive draft design for a digital queuing system, which can serve as a concrete guideline for other banks. This initial result presents a system draft enabling customers to take and monitor their queue position from anywhere. The expectation is that this solution will significantly cut waiting times and elevate the overall customer experience. As a concluding step, the system will undergo thorough testing and user satisfaction evaluation to ensure its readiness for actual implementation in the banking sector.